FAKTOR-FAKTOR PENYEBAB VARIASI PENERIMAAN PAJAK DAERAH DI INDONESIA - Noverina Angraini; Danang Adi Putra (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyze the factors causing variations in the revenue of six types of regional taxes, namely Hotel Tax, Restaurant Tax, Advertising Tax, Street Lighting Tax, Rural and Urban Land and Building Tax, as well as Taxes on Acquisition of Land and Buildings in Indonesia and their contribution to total regional tax revenue for the period 2021-2022, during the post-economic recovery period after the COVID-19 pandemic. Methods: This research employs a descriptive qualitative approach by analyzing secondary data from all regions in Indonesia for the period 2021-2022. The analysis is conducted to identify regions with the highest and lowest tax revenues and the factors that influence them. Results: The findings indicate that economic characteristics, geographic conditions, infrastructure, and regional tax policy strategies influence revenue variations. These findings are expected to provide in-depth understanding for local governments in formulating policies for optimizing tax revenue that are more targeted and in developing strategies. Strategies suitable to the characteristics of their regions. Keywords : Tax, Local Revenue, Regional Tax